VD_FINDINFO Décision / 2013 / 848 vom 16. September 2013 - VD Tribunal cantonal (2013)
ABUS DE CONFIANCE, ESCROQUERIE, DÉCISION D'IRRECEVABILITÉ, ASTUCE | 138 ch. 1 CP, 146 al. 1 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)